ORGANIC POLLUTANTS IN WATER, SEDIMENT, AND MUSCLE TISSUE OF AFRICAN CATFISH (CLARIAS GARIEPINUS BURCHELL 1822) IN AJIWA LAKE (FUDMA JOURNAL OF SCIENCES, 2024)
Organic pollution, originating from sources such as domestic activities, sewage, urban runoff, industrial effluents, and agricultural waste, introduces various organic compounds into water bodies. These compounds, including pesticides, fertilizers, hydrocarbons, and pharmaceuticals, deplete dissolved oxygen during decomposition, adversely affecting aquatic life. Persistent organic pollutants (POPs), a subset of these contaminants, are particularly concerning due to their toxicity, persistence, bioaccumulation, and long-range transport capabilities, posing significant threats to both environmental and human health. This study investigates the extent of organic pollution, focusing on POPs in Ajiwa Lake, Nigeria. The primary objectives are to identify the sources and pathways of these pollutants and evaluate their concentrations in different mediums. Fresh, mature adult African catfish (Clarias gariepinus) were collected from four sampling stations within the lake and analysed using Gas Chromatography-Mass Spectrometry (GC-MS) to determine the presence of organic pollutants. Results indicated the presence of various organic compounds in fish tissues and sediment samples, with notable pollutants including 1,2-Benzenedicarboxylic acid bis(2-ethylhexyl) ester and Hexadecanoic acid methyl ester. These compounds were detected in significant concentrations, highlighting industrial and agricultural runoff as major sources of contamination. The sediment samples further revealed high levels of pollutants like Oleic Acid and Benzene methyl, underscoring the widespread contamination in the lake. In conclusion, the findings emphasize the urgent need for effective pollution control and environmental protection strategies to mitigate the impact of POPs in Ajiwa Lake. Comprehensive monitoring and targeted interventions are crucial to safeguarding both ecosystem and human health from the adverse effects of organic pollution.
Keywords: Clarias gariepinus; Organic pollution; Organic compounds; Freshwater Ecosystem; Gas Chromatography-Mass Spectrometry (GC-MS)